Diversity and distribution of antibiotics and antibiotic resistance genes in seven national mangrove nature reserves, South China. (September 2020) - Liu, Tiankai; Lun, Jingsheng; Zheng, Peng; Feng, Jiarong; Meng, Shanshan; Peng, Tao; Hu, Zhong
Abstract: Mangrove is a complex ecosystem often affected by anthropogenic activities and receiving various antibiotics and antibiotic resistance genes (ARGs). In this study, profiles of antibiotics and ARGs of seven National Mangrove Reserves in south China were investigated. Fourteen antibiotics belonging to five categories were detected by LC-MS and twelve gene families of ARGs were evaluated by GeoChip assay. Each antibiotic category, including sulfonamides, tetracyclines, fluoroquinolones, macrolides and chloramphenicols, could be detected in all seven mangroves. In the surface sediment, the detection frequency of fourteen antibiotics was higher than 85%, except for chlorotetracycline (57%). The total antibiotic concentrations were at a high level (>250 ng/g) in the mangrove sediment of Fangchenggang (501 ng/g), Hong Kong (368 ng/g), Zhanjiang (311 ng/g) and Shenzhen (268 ng/g). High concentrations of fluoroquinolones (ciprofloxacin, norfloxacin, ofloxacin and enrofloxacin) were observed in Fangchenggang (227.7 ng/g), Beihai (85.7 ng/g), Zhanjiang (108.8 ng/g), Shenzhen (119.2 ng/g), Hongkong (126.6 ng/g) and Yunxiao (93.0 ng/g). The results suggest a widespread of antibiotic pollution in these mangroves. All ARGs families were detected in all mangroves investigated in this study. The major ARGs were multidrug resistance genes (MRGs), which accounted for more than 90% of the total ARGs abundance. These MRGs, including MATE, MFS, SMR, Mex and ATR, are families of multidrug transporters related to the transport of various antibiotics. Actinobacteria and Proteobacteria were the dominant microbial clades of the hosts for major ARGs in these mangroves. The concentration of ciprofloxacin was positively correlated with the abundance of relevant ARGs (quinolone resistance determinant). This work provides a profile of antibiotics and ARGs for further study on prevalence and proliferation of these pollutants in the mangrove ecosystems. Highlights: Occurrence of antibiotics and ARGs were investigated in seven National Mangrove Nature Reserves of South China. A widespread of antibiotic pollution was observed in these mangroves. Fluoroquinolones were the predominant antibiotics among 14 of them analyzed. More than 90% of ARGs were multidrug resistance genes. Actinobacteria and Proteobacteria were the dominant microbial clades hosting the major ARGs.